Studi Terhadap Nilai Public Relations Dalam Film Thank You For Smoking - M. Aidil Fitrah; Zulkifli Abdurrahman Usman (Sadida Islamic Communications and Media Studies, 2021)
Film is a form of mass communication. Film is a medium that has a strong influence on points of view, assumptions, perceptions, behavior, social systems in society. Without realizing what is presented in each discourse, tucked in the values of public relations which indirectly affect the demands of consumers. As in the Thank You For Smoking series directed by Jason Reitman in, not for entertainment, public relations values are inserted in several scenes that represent the role of the Public Relations Officer character in the film, such as a representation constructed by a mass media.The purpose of the study is to convey public relations values in a scene in the film Thank You For Smoking. To study the film Thank You For Smoking, the author uses a research method qualitative descriptive approach with content analysis. The data obtained through literature study, Internet searching and observation.